2009
DOI: 10.1242/dev.031815
|View full text |Cite
|
Sign up to set email alerts
|

An essential role for the RNA-binding protein Smaug during theDrosophilamaternal-to-zygotic transition

Abstract: Genetic control of embryogenesis switches from the maternal to the zygotic genome during the maternal-to-zygotic transition (MZT), when maternal mRNAs are destroyed, high-level zygotic transcription is initiated, the replication checkpoint is activated and the cell cycle slows. The midblastula transition (MBT) is the first morphological event that requires zygotic gene expression. The Drosophila MBT is marked by blastoderm cellularization and follows 13 cleavage-stage divisions. The RNA-binding protein Smaug i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
196
0
8

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 133 publications
(215 citation statements)
references
References 52 publications
11
196
0
8
Order By: Relevance
“…Consistent with this hypothesis, increasing or decreasing the maternal dosage of the string and twine genes -and thus of maternal string and twine mRNA levels -results in an increase or decrease, respectively, in the number of nuclear cycles that occur prior to blastoderm cellularization (Edgar and Datar, 1996). Also consistent with this hypothesis, embryos produced by smaug mutant females, in which cell cycle mRNAs such as Cyclin A and B fail to be eliminated, continue to undergo very rapid nuclear cycles without slowing and pausing as in wild-type embryos (Benoit et al, 2009). …”
Section: Functions Of Maternal Transcript Destabilizationmentioning
confidence: 68%
See 3 more Smart Citations
“…Consistent with this hypothesis, increasing or decreasing the maternal dosage of the string and twine genes -and thus of maternal string and twine mRNA levels -results in an increase or decrease, respectively, in the number of nuclear cycles that occur prior to blastoderm cellularization (Edgar and Datar, 1996). Also consistent with this hypothesis, embryos produced by smaug mutant females, in which cell cycle mRNAs such as Cyclin A and B fail to be eliminated, continue to undergo very rapid nuclear cycles without slowing and pausing as in wild-type embryos (Benoit et al, 2009). …”
Section: Functions Of Maternal Transcript Destabilizationmentioning
confidence: 68%
“…miR-430 requires additional, zygotically produced, nonmiRNA factors to degrade a subset of its targets (Ferg et al, 2007). The D. melanogaster miR-309 family of miRNAs, which are synthesized zygotically in a SMG-dependent manner, participate in the destabilization of several hundred maternal mRNAs in a manner analogous to that of zebrafish miR-430 (Benoit et al, 2009;Bushati et al, 2008). Beyond these studies, it has been shown in D. melanogaster that genomic loci that map to different chromosome arms are required for the destabilization of distinct subsets of maternal mRNAs (De Renzis et al, 2007).…”
Section: Mechanisms Of Maternal Transcript Destabilizationmentioning
confidence: 99%
See 2 more Smart Citations
“…S1 in the supplementary material), and prevents the production of larval cuticle. Smaug has recently been shown to be crucial for mediating the maternal-to-zygotic transition in Drosophila, and many of its additional targets are involved in regulating the cell cycle (Benoit et al, 2009). Our results with Nvsmaug indicate that many of the targets of Smaug regulation may have been conserved across holometabolan insect phylogeny.…”
Section: Research Article Nanos Function In Nasoniamentioning
confidence: 99%